Whither to ? : A Case for the Joint forest Management Model of Community forestry in West Bengal - Deb, Sudeep Budhaditya (Indian Forester, 2014)
"People-partnered, Govt.-owned" Joint Forest Management model of participatory benefit-sharing forest protection in India is under threat, even in West Bengal, where it had overwhelmingly been successful. Rising opportunity cost, due to the differential generated from spiraling appreciation in alternate use value of the forest lands and produce, visÃ - vis stagnancy in the volume of accruable per-capita stipulated benefits available from protecting the forests, is one of the major deterrents in this respect. To offset this, the hypothetical possibility of enhancing benefits by linking this with the newly emerging financial avenues like the REDD+ payments regime, etc. has its limitations. Excessive value addition to these resources may attract risks of dispossession to the participating communities. Alongside this, forest-fringe community development, resulting from the on-going JFM-support programme, has caused economic upliftment of the people in certain areas, that has generated a potency towards greater community assertion. Thus in accordance with the Herzberg's Two-factor Theory, enhancement of benefits to the community should go hand in hand with policy reforms, ensuring greater devolution of tenural, benefit-sharing and other participatory rights, to sustain JFM regime into the future.